Justice in rural carbon transition: A micro-level diagnosis from a low-carbon demonstration village in east China - Wang, Xinxin; Hong, Jingjing; Chen, Kevin Z. (CGIAR System Organization, 2025)
Based on China’s “dual-carbon” goals, rural areas are rapidly advancing toward low-carbon transition. However, uniform policy instruments may unintentionally intensify the structural inequities in how carbon burdens and resource benefits are distributed across different social groups at the micro level. Using Qingshan Village in Zhejiang Province as a case study, this study draws on a complete household survey of 738 rural families to examine the core question of carbon fairness—who bears the burden and who receives the benefits in the rural low-carbon transition. Theoretically, the study integrates the three-dimensional framework of environmental justice with the survival–luxury emissions theory to analyze the mechanisms of carbon inequality within rural communities from both distributive and recognition perspectives. Methodologically, it pioneers a micro-level carbon fairness assessment system constructed across economic, ecological, and social dimensions, and employs the entropyweight method, inter-group comparative analysis, and OLS regression to systematically identify fairness disparities among different population groups. Results show that: Clear differences in carbon fairness scores exist across income levels, gender of household head, age groups, spatial locations, and digital skills, revealing an inverse pattern of “high emissions–high gains” versus “low emissions–low gains.” Significant within-group mobility challenges the assumption of group homogeneity, highlighting the role of individual behavior and lifestyle in shaping fairness outcomes. The EBR indicator effectively differentiates survival emissions—typical among low-income and elderly households—from luxury emissions, avoided by some high-income households through intentional lowcarbon choices. The study recommends establishing differentiated carbon compensation mechanisms based on group-specific characteristics to promote a more equitable and inclusive rural low-carbon transition.